Penggunaan Algoritma C4.5 Untuk Penentuan Pemberian Pinjaman Pada Anggota Koperasi - Mohammad Dwi Arianto; Arief Jananto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
A cooperative is a financial institution with business activities of receiving deposits and providing money loans to its members. Bhina Raharja Purbalingga Savings and Loan Cooperative is a cooperative engaged in savings and loans business which was established in 1994 and has obtained the approval of a National Legal Entity, with legal entity number 12198 / BH / Vi / 1994. The activity of applying for loans in cooperatives is the most important thing to do so that there is no overpayment of installments in the future by members, the results of the analysis of the feasibility of providing loans are the determinants of the loan application submitted. In this study, it used the c4.5 algorithm for analyzing the feasibility of lending to members. The results of the analysis show that the income attribute is the attribute with the highest value with a Confusion Matrix accuracy rate of 85.34%.